Quantum-sized BiVO4 modified TiO2 microflower composite heterostructures: Efficient production of hydroxyl radicals towards visible light-driven degradation of gaseous toluene - Sun, J.; Li, Xin Yong; Zhao, Q.; Tadé, Moses; Liu, Shaomin (2015)
© The Royal Society of Chemistry 2015. In an effort to develop visible-light-driven heterostructured photocatalysts with high activity, a novel quantum-sized tubelike BiVO4 sensitized TiO2 microflower catalytic system was successfully fabricated by using a facile hydrothermal and ultrasonic adhering approach. The structural and optical properties of the as-prepared samples were comparatively characterized. The staggered band structure of quantum-sized BiVO4 decorated TiO2 not only extended the photo-response range but also promoted photoexcited charges transfer and separation. Photocatalytic activities of the as-prepared samples were examined by the degradation of toluene under visible light irradiation (? > 400 nm). Compared to the individual TiO2 microflower, BiVO4 quantum tube, BiVO4 nanoparticle and nano-BiVO4/TiO2, the quantum-BiVO4/TiO2 (Q-BiVO4/TiO2) composite exhibited higher photo activities. Electron spin resonance (ESR) examinations confirmed the generation of the photo-induced reactive oxygen species (OH and O2 -) which were involved in the photocatalytic process of Q-BiVO4/TiO2 composites. Furthermore, the enhanced photocatalytic activity of the Q-BiVO4/TiO2 composite mainly originated from the high separation efficiency of photo-induced electron-hole pairs and the efficient production of hydroxyl radicals. A detailed mechanism accounting for the superior photocatalytic activity was proposed in terms of the energy band structures of the components.